Exploring The Effectiveness of Hilokal Application on Speaking Skill Development for College Student - Aini, Nurul; Ubaidillah (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This study investigates the effectiveness of the Hilokal application in increasing speaking abilities among college students. The study took a qualitative approach, employing in-depth interviews with 30 people. The goal was to evaluate Hilokal's usability, its impact on speaking abilities, and the level of awareness among college students. According to the findings, Hilokal was seen as a user-friendly tool, with users praising its intuitive interface and ease of use. Participants reported varied amounts of improvement in their speaking skills, with some reporting strong, moderate, or low impacts. Furthermore, the survey emphasized the need for increased Hilokal knowledge among college students, since a sizable majority of participants were still unfamiliar with the application. The findings complement to our understanding of language learning technologies and have implications for educators and developers in optimizing the use of Hilokal in college settings to improve speaking skills. The findings underline the need of a user-friendly design and show Hilokal's potential benefits in promoting speaking skill development. Efforts to generate awareness and market the application, on the other hand, are critical to ensuring its widespread acceptance among college students.